Physicochemical changes in windrow co-composting process of oil palm mesocarp fiber and palm oil mill effluent anaerobic sludge - Lim, Siong Hock; Samsu Baharuddin, Azhari; Ahmad, Mohd Najib; Md. Shah, Umi Kalsom; Abdul Rahman, Nor'aini; Abd. Aziz, Suraini; Hassan, Mohd Ali; Shirai, Yoshihito (American-Eurasian Network for Scientific Information, 2009)
The objective of this study is to investigate the characteristics and physicochemical changes in windrow co-composting process of oil palm mesocarp fiber (OPMF) and palm oil mill effluent(POME) anaerobic sludge at pilot scale. The addition of POME anaerobic sludge as a nutrient source and microbial seeding into the OPMF compost led to the prolonged of thermophillic condition (50– 68°C) until day 39 of treatment. The pH value was remained stable (6.8-7.8) throughout the process whereas the moisture content was reduced towards the end of treatment with final moisture content around 50%. The final matured compost was achieved within 50 days with C/N ratio of 12.6. In addition, considerable amount of nutrients and low level of heavy metals were detected in the final matured compost. The results is indicated that windrow co-composting of OPMF and POME anaerobic sludge could produce acceptable quality of compost that can be used as fertilizer or soil amendment.